The Role of Digital Technology to Enhance Zakat, Infaq, Sadaqah and Humanitarian Fund (ZISKA) Fundraising - N. Al Ngizati Ngama Yasifah; Makhrus Makhrus (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This study examines the role of digital technology in increasing ziska fundraising. It also also reveals the inhibiting and supporting factors pertaining to ziska fundraising in zakat management organizations. This research is of field research with a descriptive approach. The object of research is Badan Amil Zakat (BAZNAS) Banyumas Regency, Lembaga Amil Zakat Infaq dan Sodaqah Muhammadiyah (LAZISMU) Banyumas Regency, and Lembaga Amil Zakat Infaq dan Sodaqah Nahdlatul Ulama (LAZISNU) Banyumas Regency. The techniques used to obtain data are observation, interviews, and documentation. The result shows that ziska fund collection is carried out through conventional methods or visiting the office, accessing Instagram, Tiktok, Google, Website, QRIS (Quick Response Code Indonesian Standard), print media, transfer via account number, pick-up zakat, UPZ (Zakat Management Unit) service, Simba application, digital office, Kitabisa. Meanwhile, LAZISNU uses Koin NU (Nahdlatul Ulama Infaq Can). As for the supporting factors, there are social media or print media and even applications that can support the running of ziska fund collection, while the inhibiting factors are the lack of understanding for ordinary people and the lack of internal expertise in special fields to carry out socialization to the community.